Tooth in the nose (Bangladesh Journal of Medical Science, 2014)
The finding of intranasal ectopic or supernumerary tooth although have been reported in the past, is still considered a rare presentation. It may remain silent for a long period of time, before manifesting with nasal symptoms. We report the case of a 33-year-old lady with an ectopic pre-molar tooth in the floor of her right nostril, presenting with intermittent epistaxis and foul-smelling nasal discharge. She was referred for a rhinolith in her nose. The tooth was successfully extracted via intranasal endoscopic approach. DOI: http://dx.doi.org/10.3329/bjms.v13i3.19157 Bangladesh Journal of Medical Science Vol.13(3) 2014 p.336-339